Out‐Of‐Plane Ordered Laminate Borides and Their 2D Ti‐Based Derivative from Chemical Exfoliation. Issue 38 (5th August 2021) - Dahlqvist, Martin; Zhou, Jie; Persson, Ingemar; Ahmed, Bilal; Lu, Jun; Halim, Joseph; Tao, Quanzheng; Palisaitis, Justinas; Thörnberg, Jimmy; Helmer, Pernilla; Hultman, Lars; Persson, Per O. Å.; et al.
Abstract: Exploratory theoretical predictions in uncharted structural and compositional space are integral to materials discoveries. Inspired by M 5 SiB2 (T2) phases, the finding of a family of laminated quaternary metal borides, M ′4 M ″SiB2, with out‐of‐plane chemical order is reported here. 11 chemically ordered phases as well as 40 solid solutions, introducing four elements previously not observed in these borides are predicted. The predictions are experimentally verified for Ti4 MoSiB2, establishing Ti as part of the T2 boride compositional space. Chemical exfoliation of Ti4 MoSiB2 and select removal of Si and MoB2 sub‐layers is validated by derivation of a 2D material, TiO x Cl y, of high yield and in the form of delaminated sheets. These sheets have an experimentally determined direct band gap of ≈4.1 eV, and display characteristics suitable for supercapacitor applications. The results take the concept of chemical exfoliation beyond currently available 2D materials, and expands the envelope of 3D and 2D candidates, and their applications. Abstract : Out‐of‐plane chemical order in layered T2 phase Ti4 MoSiB2 ( o ‐MAB) is theoretically predicted and experimentally verified. Chemical exfoliation of the compound is shown by derivation of a 2D material, TiO x Cl y . The 2D sheets have a direct bandgap of ≈4.1 eV and display characteristics suitable for supercapacitor applications.